Alternative methods for anaerobic power assessment in athletes: A correlational study of Wingate, vertical jump, and standing broad jump tests - Joshi, K.; Singh, A. (Polish Journal of Sport and Tourism, 2024)
Introduction. Power plays a vital role in various sporting activities in which the aerobic system produces the most energy. However, anaerobic power is vital when the player demands an immediate energy supply. The primary goal of this study is to determine whether the standing broad jump (SBJ) and vertical jump (VJ) tests can be correlated with those of the Win-gate ergometry test so that a reliable and cost-effective method for athlete monitoring and skill identification is available.